Constructing a Multidimensional Financial Stability Index: A Focus on Internal and External Drivers in Developing Nations (Journal of Asian Development Studies, 2024)
This study constructs a financial stability index for various developing countries using data from 2005 to 2020, revealing varying levels of financial stability across nations and years. The study uses weighted average methods of index construction followed by UNDP. The study uses some internal and external elements of financial stability to construct the index. The findings indicate that most developing countries, including Albania, Algeria, Angola, Argentina, Bangladesh, and others, have consistently low financial stability scores throughout the period. A few countries, such as Belize, Brazil, China, and Malaysia, have experienced fluctuations, with instances of medium-level financial stability. Notably, China stands out as the only developing country achieving high financial stability, particularly after 2012, with an increasing trend peaking at 54.79 in 2020. The overall results highlight that, except for China, developing countries struggle to attain a high level of financial stability, mainly remaining within the lower or medium stability brackets. The study emphasizes the need for developing countries to enhance economic activities and infrastructure to improve their financial stability. Achieving this would require comprehensive policy measures to foster economic growth, improve access to finance, and promote financial inclusivity. The findings underscore the importance of structural and policy reforms in driving financial stability, which is crucial for sustainable development. This study highlights that by constructing a multidimensional index incorporating these internal and external factors, policymakers and researchers can better assess the financial stability of developing countries. This index provides a more comprehensive understanding of the financial system's strengths and weaknesses, allowing for more targeted policy interventions to enhance financial stability.